INVESTIGATION OF DIFFERENT CURING TEMPERATURES ON PHASE CHANGES DURING DRYING OF CASTABLES - Köhler, Andreas; Kuiper, S.; Klaus, S.; Götz-Neunhoeffer, Friedlinde (Unified International Technical Conference on Refractories, UNITECR 2022 - Proceedings, 2022)
In this study, the influence of different curing temperatures on the subsequent phase changes during the drying process of calcium aluminate cement bond castables is presented. A mixture of CAC and alumina was hydrated at different temperatures (5, 23, 40°C), which should represent extreme working conditions during casting. The quantitative phase composition after 48 h of hydration was determined by Rietveld-analysis. Thermogravimetric analysis was also used to characterize the weight loss during heating. The results have shown that above 350 °C all hydrate phases are dehydrated, but that the differently cured samples lead to quite different dehydration processes and phase compositions. Therefore, the cured samples were heated up to 180 °C, as at this temperature the different curing conditions lead to a different dehydration progress. The different starting conditions before drying strongly affect the final phase composition, as well as a different way to get the water-free product. Samples cured at moderate or high temperature lose water over a wider temperature range. In contrast, in samples cured at low temperature, almost all unbound H2O and water in hydrate phases is removed at temperatures below 180 °C.
CRIS-Team Scopus Importer:2024-12-16